Let f be a function from positive integers to positive integers satisfying f(n+1)>f(n) and f(f(n))=3n for all positive integers n. Calculate f(k) for k=1,…,10.
This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.
When posting on Brilliant:
Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.
Markdown
Appears as
*italics* or _italics_
italics
**bold** or __bold__
bold
- bulleted - list
bulleted
list
1. numbered 2. list
numbered
list
Note: you must add a full line of space before and after lists for them to show up correctly
@Jeff Giff Here is their given Solution: To solve this type of problem, one tries to find solutions for n = 0, or n = 1 and/or some other property of f. Then one can conjecture more values, and more general results can usually be proved by induction. In this case, only low-order results are sought, so no inductive proof of general results is needed.
We start by showing f(1) > 1, as if f(1) = 1, we would have 3 = f(f(1)) = 1, a contradic- tion.
More generally, f(n) > n, for if f(n) ≤ n for some n = k we would have f(k−1) < f(k) ≤ k, so f(k − 1) ≤ k − 1. Repeat this argument k − 1 times and we obtain f(1) ≤ 1, in contra- diction to our result above. Hence f(n) > n for all n. f(1)=2.Supposef(1)=m≥3.Then3=f(f(1))=f(m)>m≥3,acontradiction. So f(1) = 2.
So now from the given properties of f we can calculate several values:
f(2) = f(f(1)) = 3, f(3) = f(f(2)) = 6, f(6) = f(f(3)) = 9, f(9) = f(f(6)) = 18.
Giventhat6=f(3)<f(4)<f(5)<f(6)=9,itfollowsthatf(4)=7, f(5)=8,so f(7) = f(f(4)) = 12 and f(8) = f(f(5)) = 15. Now f(18) = f(f(9)) = 27, and as there are 8 unknown values between f(9) = 18 and f(18) = 27 and 8 numbers between 18 and 27, it follows that f(10) = 19, f(11) = 20, ··· f(17) = 26.
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Consider f(x)=kx+b, k=3 and b=0. But it says positive integers...
Log in to reply
@Jeff Giff Here is their given Solution: To solve this type of problem, one tries to find solutions for n = 0, or n = 1 and/or some other property of f. Then one can conjecture more values, and more general results can usually be proved by induction. In this case, only low-order results are sought, so no inductive proof of general results is needed. We start by showing f(1) > 1, as if f(1) = 1, we would have 3 = f(f(1)) = 1, a contradic- tion. More generally, f(n) > n, for if f(n) ≤ n for some n = k we would have f(k−1) < f(k) ≤ k, so f(k − 1) ≤ k − 1. Repeat this argument k − 1 times and we obtain f(1) ≤ 1, in contra- diction to our result above. Hence f(n) > n for all n. f(1)=2.Supposef(1)=m≥3.Then3=f(f(1))=f(m)>m≥3,acontradiction. So f(1) = 2. So now from the given properties of f we can calculate several values: f(2) = f(f(1)) = 3, f(3) = f(f(2)) = 6, f(6) = f(f(3)) = 9, f(9) = f(f(6)) = 18. Giventhat6=f(3)<f(4)<f(5)<f(6)=9,itfollowsthatf(4)=7, f(5)=8,so f(7) = f(f(4)) = 12 and f(8) = f(f(5)) = 15. Now f(18) = f(f(9)) = 27, and as there are 8 unknown values between f(9) = 18 and f(18) = 27 and 8 numbers between 18 and 27, it follows that f(10) = 19, f(11) = 20, ··· f(17) = 26.
Log in to reply
Oh, yeah! I forgot that it could be random :P
Here are some things we know: